Analisa Keuangan Kelayakan Pengembangan Kawasan Wisata Terpadu Bangsalae di Kabupaten Wajo - Wanma, Alvany Theresia; Fadhillah, Prayudhi (ACE: Accounting Research Journal, 2025)
ABSTRACT The Bangsalae area in Siwa Village, Pitumpanua District, Wajo Regency, is a coastal area that has high economic, social, and ecological potential to be developed as a marine tourism destination. Previously, this area functioned as a Fisheries Port (PPI) based on the Decree of the Minister of Maritime Affairs and Fisheries Number 120 of 2021. However, the decline in fishery activities has prompted the Wajo Regency Government to transform the area's function into the Bangsalae Integrated Tourism Area, as outlined in the Regent of Wajo's Decree Number 562/U/2025, as part of a regional strategic project. This research aims to assess the feasibility of the project from a financial point of view in the development of the area. The study was conducted through the analysis of primary and secondary data, including interviews, field surveys, and regional and national policy reviews. The total investment is IDR 17,000,000,000.00 with an estimated 8-year actual term and a discount rate of 8%. Financial analysis is carried out by making cash flow projections and then calculating using the project feasibility analysis tool, where, financially, this project is considered feasible with a Net Present Value (NPV) of IDR 8.4 billion, Internal Rate of Return (IRR) of 20%, Benefit-Cost Ratio of 1.49, and Payback Period of 4 years, ROI of 26%. Keywords: Feasibility Study, Investment, Financial Analysis ABSTRAK Kawasan Bangsalae di Kelurahan Siwa, Kecamatan Pitumpanua, Kabupaten Wajo, merupakan wilayah pesisir yang memiliki potensi ekonomi, sosial, dan ekologi tinggi untuk dikembangkan sebagai destinasi wisata bahari. Sebelumnya, kawasan ini berfungsi sebagai Pelabuhan Perikanan (PPI) berdasarkan Keputusan Menteri Kelautan dan Perikanan Nomor 120 Tahun 2021. Namun, menurunnya aktivitas perikanan mendorong Pemerintah Kabupaten Wajo untuk melakukan transformasi fungsi kawasan menjadi Kawasan Wisata Terpadu Bangsalae melalui SK Bupati Wajo Nomor 562/U/2025 sebagai bagian dari proyek strategis daerah. Penelitian ini bertujuan untuk menilai kelayakan proyek dari segi keuangan dalam pengembangan kawasan tersebut. Kajian dilakukan melalui analisis data primer dan sekunder, baik wawancara, survei lapangan, dan telaah kebijakan daerah serta nasional. Total investasi sebesar Rp 17,000,000,000.00 dengan estimasi jangka aktu 8 tahun dan discount rate 8%. Analisa keuangan dilakukan dengan membuat proyeksi cash flow lalu dihitung dengan alat Analisa kelayakan proyek dimana secara finansial, proyek ini dinilai layak dengan Net Present Value (NPV) sebesar Rp 8,4 miliar, Internal Rate of Return (IRR) 20%, Benefit-Cost Ratio 1,49, dan Payback Period 4 tahun, ROI 26 %. Kata kunci: Studi Kelayakan, Investasi, Analisa Keuangan